2020
DOI: 10.3390/ijms21062092
|View full text |Cite
|
Sign up to set email alerts
|

The Pervasive Role of the miR-181 Family in Development, Neurodegeneration, and Cancer

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs playing a fundamental role in the regulation of gene expression. Evidence accumulating in the past decades indicate that they are capable of simultaneously modulating diverse signaling pathways involved in a variety of pathophysiological processes. In the present review, we provide a comprehensive overview of the function of a highly conserved group of miRNAs, the miR-181 family, both in physiological as well as in pathological conditions. We summarize a large body o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 145 publications
(263 reference statements)
3
117
0
1
Order By: Relevance
“…miRNAs are widely involved in cell proliferation, organ development, immune response and tumor formation among other processes. Previous studies reported that miRNAs are closely related to the occurrence and development of certain types of tumor ( 35 - 37 ). Not only they can function as tumor promoters but they can also function as oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are widely involved in cell proliferation, organ development, immune response and tumor formation among other processes. Previous studies reported that miRNAs are closely related to the occurrence and development of certain types of tumor ( 35 - 37 ). Not only they can function as tumor promoters but they can also function as oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer, a positive feedback loop between miR-181b and STAT3 was identified, which regulated the Warburg effect and xenograft tumor growth (20). It has been well documented that the expression of miR-181b in glioblastoma, where it acts as an onco-suppressor gene, is downregulated via the NF-κB pathway (5). The NF-κB signaling pathway plays a key role in colon cancer cell proliferation and apoptosis (14).…”
Section: Discussionmentioning
confidence: 99%
“…At present, microRNAs (miRNAs or miRs), types of small non-coding RNAs of 20-24 nucleotides in length, have gained increasing attention due to their regulatory effects on the transcription of their target genes (5). A large number of studies have suggested that miRNAs regulate fundamental biological processes, while their dysfunction may affect the balance of the human body, which in turn induces tissue/organ injuries (5,6). Among the miRNA families, the present study aimed to investigate the role of miR-181b in colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These common mechanisms can explain the similar retinal phenotype seen in patients with PD and those with LHON and DOA, suggesting that they might also share similar therapeutic targets. Strategies that enhanced mitophagy and mitochondrial biogenesis resulted indeed in an amelioration of the phenotype in both LHON and PD representing attractive targets for drug development (Zheng et al, 2010;Dikic and Bremm, 2014;Eschbach et al, 2015;Koentjoro et al, 2017;Indrieri et al, 2019Indrieri et al, , 2020.…”
Section: Molecular Mechanisms Implicated In Pd Visual Abnormalitiesmentioning
confidence: 99%